Security and Privacy Preservation in Smart Cities During Security Surveillance: A Mapping Study - Fatima Tariq; Ayesha Afzaal; Muhammad Junaid Anjum; Faria Kanwal; Komal Bashir; Momina Shaheen (Applied Computational Intelligence and Soft Computing)
As smart cities have evolved through the constant incorporation of advanced technologies such as Internet of Things, the importance of efficient data collection and robust security monitoring has increased massively. These smart cities, while monitoring and evaluating different activities, utilize a network of interconnected sensors and devices. This would not only enhance the provision of public services but also ensure increased safety measures. However, the extensive implementation of such systems has increased the concerns related to privacy and data protection. The growing dependence on surveillance technology in smart cities, though beneficial in terms of security, has also increased challenges associated with the protection of individual privacy. As such, different research has been conducted to develop advanced solutions that ensure the security of an individual while also safeguarding their personal privacy. This study examines the different aspects of privacy preservation in the context of security surveillance in smart cities. By conducting a comprehensive analysis of 100 research articles, it elucidates the current state of research and identifies emerging solutions aimed at safeguarding citizen privacy while simultaneously upholding the integrity of smart urban environments.